El concepto pedagógico "formación" en el universo semántico de la educación - Venegas Renauld, María Eugenia (2011)
This article includes the findings of a research study on the formation concept included in the Fundamental Law of Costa Rican Education. The research questions seek to find the roots of this concept in the Western world. Along with the scanning of educational language, the semantic approach is used as a scanning step. This articles shows the semantic complexity of the term in a wide range of notions and explores the great possibility of lexical bridges that can be established with similar or related terms.